Surveillance in Urban Nightscapes. A STS-Informed Perspective - Timan, Tjerk (Tecnoscienza – Italian Journal of Science & Technology Studies, 2013)
In the project “Surveillance in Urban Nightscapes”, surveillance practices during the night are investigated in Dutch city centers. Besides organizational surveillance technologies such as Cctv and bodycameras, bottom-up image technologies are invading this nightscape (Octv), in the form of mobile cameras. This shared footage affects both citizens who go for a night out – you never know when and where you might have been filmed – as well as organizational surveillance – the amount of sources for watching and reconstructing events that take place in the city centre increases. Theoretically, this can be seen as gradual change in the landscape of surveillance in (nightly) public spaces. This literature review tries to capture and combine different concepts from three disciplines: urban geography, surveillance and STS. The concluding remarks deal with key concepts derived from combinations of literature and tries to explain why and how a STS-informed analysis is necessary when investigating surveillance in urban nightscapes.